Assessment of the competitive position of foreign thermal coal trade in European countries in 2010–2023 - Kubala, Sebastian; Stanuch, Marcin; Kornaś, Wioletta (Research Papers in Economics and Finance, 2025)
The main objective of this study was to present changes in the competitiveness of foreign thermal coal trade in European countries in the years 2010–2023. The research used the adjusted RCA index, the Trade Coverage Index and the Import Penetration Index. The research results indicate that there has been a dynamic and diversified nature of the changes in the competitive position of foreign coal trade in Europe. Although many European countries are gradually moving away from the use of coal, there are still countries that maintain competitiveness in this market, in particular Russia.